2022
DOI: 10.3390/su141912696
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Local Agents and Citizens to Sustainable Development: The Portuguese Experience

Abstract: The achievement of the 2030 Agenda implies a shared responsibility in the implementation of the Sustainable Development Goals (SDGs). Local government, in particular municipalities, is closer to citizens and, therefore, better placed to respond to the needs of each region. This study intends to explore initiatives promoted by civil society, businesses, and local organizations in the context of each municipality in Portugal to address the sustainable development goals established in the 2030 Agenda. It adopts m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Local actors can work through networks and establish synergies between projects that may broaden initiatives' coverage through civil society, businesses, and local organizations [38]. The present research found that prior studies have included university-government partnerships fostering a culture of entrepreneurial initiatives [51] and relationships between governments and non-governmental entities focusing on a coherent conceptual approach to sport and development [52].…”
Section: Government Areamentioning
confidence: 71%
See 1 more Smart Citation
“…Local actors can work through networks and establish synergies between projects that may broaden initiatives' coverage through civil society, businesses, and local organizations [38]. The present research found that prior studies have included university-government partnerships fostering a culture of entrepreneurial initiatives [51] and relationships between governments and non-governmental entities focusing on a coherent conceptual approach to sport and development [52].…”
Section: Government Areamentioning
confidence: 71%
“…Implementing the 2030 Agenda can only be carried out by multiple organizations' sharing the responsibility for reaching the SDGs. LPAs are closer to citizens, so they are better positioned to respond to each municipality or local community's needs [38]. Within the 2030 Agenda's framework, LPAs should implement initiatives in communities-after identifying their specific challenges and priorities-by adapting and localizing SDGs, also referred to as the operationalization of the SDGs [39].…”
Section: Government Areamentioning
confidence: 99%
“…This study involved conducting a survey among SMEs in Portugal and the UK. The survey was shared with SMEs registered with the Small Business Support Institute in both countries, and a total of 249 responses were received after removing incomplete responses [24] the understanding of the factors influencing green innovation and economic performance in small enterprises and provides insights for policymakers and organizations to support and promote green entrepreneurship in Saudi Arabia [25] eco-innovation plays a crucial role in transitioning towards a more resource-efficient economy. The eco-innovation index is an important indicator of environmental innovation, research, and development, and is one of the thematic indicators in the European Union's Resource Efficiency Scoreboard [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Today's cities require a change in urban planning to address the complex relationships between citizens' interests and needs, urban transformations, environmental degradation, urban policies, and economic interests in a sustainable approach [1]. Social innovation is one of the pillars of sustainability that is becoming increasingly important as one of the dimensions that merit a multidisciplinary and transversal approach [2][3][4][5][6][7][8][9], where the active participation of citizens is required not only as recipients [10] but also as co-creators of their reality. In this sense, a series of mechanisms and strategies have emerged that seek to involve citizens in decision-making processes in the city, such as participatory budgets, urban centres, living labs [11,12], and innovation centres, in which synergies are created between civil society, public administration, academia, and companies [13] to seek solutions to social challenges; these strategies and platforms are usually guided by public administration.…”
Section: Introductionmentioning
confidence: 99%